2019
DOI: 10.1016/j.drugpo.2019.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Chemsex is not a barrier to self-reported daily PrEP adherence among PROUD study participants

Abstract: BackgroundPre-exposure prophylaxis (PrEP) is a novel HIV prevention method whereby HIV-negative individuals take the drugs tenofovir and emtricitabine to prevent HIV acquisition. Optimal adherence is critical for PrEP efficacy. Chemsex describes sexual activity under the influence of psychoactive drugs, in the UK typically; crystal methamphetamine, gamma-hydroxybutyrate(GHB) and/or mephedrone. Chemsex drug use has been associated with increased HIV transmission risk among gay, bisexual and other men who have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 47 publications
4
29
2
Order By: Relevance
“…Additional resources for treatment of substance use disorder are needed within PrEP clinics and primary care settings, such as counselling, social workers, providers who can prescribe buprenorphine for opioid use disorder, harm reduction education, referral to syringe exchange programmes, and naloxone distribution. Although novel interventions for stimulant use disorder are needed, it should be noted that with sufficient support, stimulant users can achieve high PrEP adherence [27‐29]. One participant specifically requested that mental health services be co‐located within primary care clinics that offer PrEP [30].…”
Section: Discussionmentioning
confidence: 99%
“…Additional resources for treatment of substance use disorder are needed within PrEP clinics and primary care settings, such as counselling, social workers, providers who can prescribe buprenorphine for opioid use disorder, harm reduction education, referral to syringe exchange programmes, and naloxone distribution. Although novel interventions for stimulant use disorder are needed, it should be noted that with sufficient support, stimulant users can achieve high PrEP adherence [27‐29]. One participant specifically requested that mental health services be co‐located within primary care clinics that offer PrEP [30].…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey found that Brazilian and Portuguese MSM experience difficulty in remaining socially isolated, since 53% reported engaging in casual sex during social distancing, despite the growing risk of acquiring SARS-CoV-2, the cause of COVID-19. They also reported increased consumption of alcohol and other drugs 3,4 , sometimes associated with sex, thus chemsex 5,6 , or sexual practice under the influence of drugs and chemical substances. Widely reported among MSM 7 before the pandemic, this practice has the purpose of prolonging and enhancing pleasure from the sex act.…”
Section: Introductionmentioning
confidence: 99%
“… 7 One analysis of data from a UK PrEP effectiveness trial reported that there was no association between self-reported adherence and chemsex. 11 However, purposive research is required to explore the biopsychosocial factors which influence PrEP medication adherence among MSM chemsex participants.…”
Section: Discussionmentioning
confidence: 99%